TRADISI MENULIS Q.S. AL-QAṢAṢ: 85 DI MAKAM WALIYULLAH OLEH PESANTREN AL-UMM ASWAJA, CIAWI, BOGOR - Pratiwi, Haniefa Ayunafa (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This paper discusses the tradition of writing Q.S. al-Qaṣaṣ: 85 on the graves of saints by Al-Umm ASWAJA Islamic Boarding School, Ciawi, Bogor. The uniqueness of this tradition is that it is said to have spiritual benefits that can make the perpetrators "called back" by the grave experts who are pilgrimaged, and in this tradition they do not use writing tools at all, they only use their fingers as a writing medium. From this uniqueness, the researcher formulated the problem of this study, first, why Q.S. al-Qaṣaṣ: 85 is used in the tradition of writing at the tomb of waliyullah by Al-Umm ASWAJA Pesantren, Ciawi Bogor, and second, what are the motives and objectives of the perpetrators of the tradition of writing Q.S. al-Qaṣaṣ: 85 at the tomb of waliyullah. The research uses the analytical knife of social action theory initiated by Max Weber to analyze the reasons for using Q.S. al-Qaṣaṣ: 85 in the tradition and find out the motives and goals of the perpetrators of the tradition. This research also collected data through interviews, questionnaires, and documentation because this research is a field research.